اكتشاف طفرتين في الإكسون 28 ضمن مورثة فون فيلبراند لدى مريضين راجعا مشفى هلم شاير الجامعي - عيسى محي الدين (Latakia University Journal -Biological Sciences Series, 2013)
اكتشفت طفرتان في الإكسون 28 من مورثة فون فيلبراند لدى رجل A وامرأةB مصابين بمرض فون فيلبراند. وقد أظهرت الاختبارات النوعية مثل مقايسة ارتباط VWF:FVIII ومقايسة ارتباط الكولاجن VWF:CB وتحليل بروتين العامل VWFأن مرض VWD هو من نمط 2Aفي المورثة. كما كشف تحري الإكسون 28 بواسطة تقنيةPCR وسلسلة أسس الدنا DNA عن وجود الطفرة A1 (C>T) في المريض A والطفرة B1 (G>A) في المريضة B وهي طفرات مسؤولة عن ظهور المرض VWD مما يؤكد على أن مورثات التخثر الطبيعية هي مورثات منظمة ومبرمجة ذاتياً. Two mutations of exon 28 in the Von Willbrand gene have discovered intwopatients (female and male).Specific tests such as the VWF: FVIIIbinding assay, collagen binding assay VWF:CB and VWF proteinanalysis give that VWD is a type of 2A at the gene. Investigating exon 28 by PCR technique and DNA sequencingrevealed mutation A1(C>T) in patientA and a mutationB1(G>A) inpatientB. These mutations are responsible for the presence of VWD. Assuring that natural genes involved in coagulation are well organised and automated.